Analisis Ketuntasan Belajar Siswa Pada Mata Pelajaran IPS - Bahrin Bahrin; Rossa Ayuni (Departement of Mathematics Education, 2023)
The purpose of this research is to find out about the completeness of student learning in social studies at SMP Negeri 2 Bengkulu City. The informants in this study were 2 social studies teachers for class VII at SMP Negeri 2 Bengkulu City. Data collection techniques used are observation, interviews and documentation. In this study the data analysis technique used is percentage. The results of the research show that overall learning completeness can be known by students who have completed it by 91.08%. Students who complete means that these students take social studies subjects seriously. While students who did not achieve completeness as a whole were 8.92%. Students who do not complete means that the ability of these students is limited. To improve these grades students must take part in remedial and will be given additional assignments with the material being studied.